The changing role of the state in the Italian healthcare system - Lorraine Frisina Doetter; Ralf Götze (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2011)
The present study describes and explains the changing role of the state in the Italian healthcare system since the beginning of the 1970s, with a particular focus on developments following 1978 when the healthcare system was transformed from a social insurance system into a national health service. In order to address these changes in a systematic way, we track healthcare system development along three dimensions: regulation, financing, and service provision. With regard to regulation, we observe a relative retreat of the state due to decentralization processes and internal market mechanisms. Quantitative measures for the financing and service provision dimension also indicate a modest relative retreat of the state. Taking regional data into account, we identify a clear North-South-divide in the public/private mix of financing and service provision. Although the focus of the paper is to describe the changing role of the state in the Italian healthcare system, we also offer preliminary explanations. We seek to identify the role of exogenous shocks such as economic crises versus endogenous stressors specific to the healthcare system itself (i.e. inherent inefficiencies) on healthcare system change. Therefore, the paper aims to provide a tentative, yet dynamic account of healthcare system change that is both descriptive and explanatory. – – Dieses Papier behandelt die veränderte Rolle des Staates im italienischen Gesundheitssystem seit den 1970er Jahren. Italien vollzog zum Beginn des Untersuchungszeitraums einen Systemwechsel von einem Sozialversicherungssystem zu einem Nationalen Gesundheitsdienst. Um die anschließenden Wandlungsprozesse in systematischer Form zu erfassen, unterscheiden wir zwischen drei Dimensionen von Staatstätigkeit im Gesundheitswesen: Regulierung, Finanzierung und Leistungserbringung. In der Regulierung beobachten wir einen relativen Rückzug des Staates durch Dezentralisierungsprozesse und die partielle Einführung interner Märkte. Dieser Befund deckt sich auch mit den quantitativen Analysen zur Finanzierung und Leistungserbringung. Durch die Einbeziehung regionaler Daten zeigt sich zudem ein klares Nord-Süd-Gefälle, das sich sowohl im öffentlichen Anteil an der Finanzierung als auch an der Leistungserbringung widerspiegelt. Das Papier beschränkt sich nicht auf die Beschreibung des Staatswandels, sondern bietet auch erste Erklärungen für diese Beobachtungen. Dazu werden sowohl exogene Faktoren wie wirtschaftliche Krisen oder Europäisierung als auch endogene Stressoren wie systeminhärente Defizite betrachtet.
Keywords: 300; Gesundheitswesen; Staatliche Einflussnahme; Gesundheitsfinanzierung; Italien